Aryl acyl peroxides for visible-light induced decarboxylative arylation of quinoxalin-2(1H)-ones under additive-, metal catalyst-, and external photosensitizer-free and ambient conditions. Issue 1 (14th December 2020) - Xie, Long-Yong; Peng, Sha; Yang, Li-Hua; Peng, Cun; Lin, Ying-Wu; Yu, Xianyong; Cao, Zhong; Peng, Yu-Yu; He, Wei-Min
Abstract : Aryl radicals were generated for the first time from aryl acyl peroxides in ethyl acetate under ambient conditions and visible-light illumination in the absence of any additive, metal catalyst, or external photosensitizer. Abstract : Aryl radicals were generated for the first time from cheap and easily available aryl acyl peroxides in eco-friendly ethyl acetate under ambient conditions and visible-light illumination in the absence of any additive, metal catalyst, or external photosensitizer. The present arylation of quinoxalin-2(1 H )-ones was chemo- and regioselective, and provided good access to various 3-arylquinoxalin-2(1 H )-ones.